ASSOCIATION OF DYSLIPIDEMIA AS A RISK FACTOR FOR THE FIRST EPISODE OF ISCHEMIC STROKE - Afridi, Muhammad Abdur Rahman; Farah Rabbani; Yasmin Akhtar (Journal of Postgraduate Medical Institute, 2023)
Objective: To determine the frequency and association of dyslipidemia in patients with the first episode of ischemic stroke. Methodology: This observational, descriptive study of 126 patients of the first episode of ischemic stroke was conducted in the Medicine department of Lady Reading Hospital Peshawar from August 2020 to March 2021. After approval of the study by the hospital's Ethical Review Board, patients were enrolled by non-probability consecutive sampling technique. Relevant investigations of the patients were carried out, including fasting serum lipids and brain scan/MRI. SPSS® version 21 was used for data entry and statistical analysis; a Chi-square p-value <0.05 was considered significant. Results: A total of 126 patients, 70(55.6%) men and 56(44.4%) women with the first-ever ischemic stroke, had a mean age of 54.56 years ±9.74SD. Dyslipidemia was found in 51.6% of patients; 53.8% of men and 46.2% of women, however, the gender difference was insignificant (X2 (df1)=0.159, p=0.690). Among 51.6% of patients with dyslipidemia, hypercholesterolemia was the most common abnormality in 29.4% while raised levels of Low-density lipoproteins-cholesterol (LDL-C) were seen in 7.1% of patients. No significant difference in dyslipidemia was observed in different age groups (X2 (df3)=2.263, p=0.520). Gender-wise, ischemic stroke occurred significantly in the younger men compared to women (X2(df3)=8.762, p=0.033). Conclusion: The present study concludes that dyslipidemia was not significantly associated with patients with the first episode of ischemic stroke. Ischemic stroke occurred more significantly in younger men compared to women; however, both genders were equally affected in older age.